Differentiation of Human Leukemia Monocyte Cells to Macrophage-Like Cells with Phorbol- 12-Myristate-13-Acetate - Derya Biriken (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
Objectives:In this study, it was aimed to evaluate appropriate model of application time and dosage of Phorbol-12-Myristate-13-Acetate (PMA) to get activated macrophages from monocytic cell line THP-1 cells. The differentiation of THP-1 cells into macrophages when stimulated with different dosage and application time of phorbol myristic acid (PMA) was shown morphologically and the effects on cell viability were evaluated.Materials and Methods:THP-1 cells were produced as suspension as 2x105 cells/mL in 6-well plates. Afterwards, THP-1 monocyte cells were treated with PMA of 10, 20, 40, 60 ng/mL concentrations and incubated for 24, 48 and 72 hours. Differentiation of suspended THP-1 cells into adherent macrophage-like cells was confirmed by tissue-culture microscope by observing cell adherence to cell culture flasks and phenotypic changes. Cell viability was determined by trypan blue staining.Results and Conclusion:The best results for phenotypic changes and cell viability for THP-1 cells were obtained with 20 ng/mL PMA at 48h incubation time and the cell viability was detected as 92.2%. The administration of 40 ng/mL PMA resulted in a significant decrease in cell count compared to 10 and 20 ng/ml PMA administration at the 48h, but no difference was observed between groups after 72h application. These findings show that the differentiation of THP-1 monocytes into macrophages needs to be optimized in order to reflect the real physiologic conditions of macrophage models used in in vitro studies. These findings suggest that THP-1 cells are well differentiated by 20 ng/mL PMA at 48h incubation.